The effect of interval training on athletic 100 meter running speed: a meta-analysis study - Vindryani Septayasa; Supriatna Supriatna; Yulingga Nanda Hanief; Teejay D. Panganiban (CV Rezki Media, 2022)
This research on the effect of interval training on 100 meter running speed has been widely done in sports. Various researchers explain that interval training is very influential in increasing the speed of running 100 meters, but each study reports different results. This difference causes the need to conduct inclusive data analysis to provide comprehensive information about the importance of interval training to increase 100-meter running speed in athletic athletes. This method must be done by collecting data from research results indexed on Google Scholar by searching for research published in the range of 2010-2021. The search for the results of this study was carried out by entering two keywords, namely the first keyword